2020
DOI: 10.1039/c9em00580c
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of surfactants onto sediment at environmentally relevant concentrations:independent-mode as unifying concept

Abstract: The Independent-Mode model explains observed sorption phenomena of surfactants at low concentrations (Cs→0, Cw→0) to complex sediments better than the Dual-Mode model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 81 publications
0
14
0
Order By: Relevance
“… 11 , 12 As a consequence, there are very few BCF values for surfactants reported in the literature. 13 A review conducted in 2007 concluded that there were no useful BCF data for cationic surfactants at that time, 14 and few data have emerged since. We are aware of just two regulatory dossiers that refer to unpublished BCF studies for didecyldimethylammonium chloride and alkyl(C 12–16 )dimethylbenzyl ammonium chloride.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 , 12 As a consequence, there are very few BCF values for surfactants reported in the literature. 13 A review conducted in 2007 concluded that there were no useful BCF data for cationic surfactants at that time, 14 and few data have emerged since. We are aware of just two regulatory dossiers that refer to unpublished BCF studies for didecyldimethylammonium chloride and alkyl(C 12–16 )dimethylbenzyl ammonium chloride.…”
Section: Introductionmentioning
confidence: 99%
“…However, maintaining constant exposure concentrations has proven difficult for cationic surfactants as many of them possess a strong tendency to sorb to surfaces. , As a consequence, there are very few BCF values for surfactants reported in the literature . A review conducted in 2007 concluded that there were no useful BCF data for cationic surfactants at that time, and few data have emerged since. We are aware of just two regulatory dossiers that refer to unpublished BCF studies for didecyldimethylammonium chloride and alkyl­(C 12–16 )­dimethylbenzyl ammonium chloride. , Field bioaccumulation factors of long-chain cationic surfactants (C 13 –C 18 ) have been reported in the literature, but to a very limited extent …”
Section: Introductionmentioning
confidence: 99%
“…Near-constant aqueous concentrations (±20% of the mean) during the exposure phase are a requirement for a valid BCF experiment according to OECD 305 guidelines . A review of early BCF studies concluded that there were no useful data for cationic surfactants . The little information that there is on this subject comes largely from regulatory dossiers that refer to unpublished studies conducted to fulfill chemical registration requirements.…”
Section: Introductionmentioning
confidence: 99%
“… 6 In a second review from 2007, 38 measured BCF values for anionic surfactants representing 10 C 10 –C 13 LASs and 7 perfluoroalkyl acids were judged to be quantitatively reliable. 7 There have since been several other BCF values published for LASs. 8 10 Furthermore, BCF values from several unpublished industry studies have been reported, whereby few details are available on the methodology employed.…”
Section: Introductionmentioning
confidence: 99%
“…However, a review of the available data in 1994 concluded “Most of these data are inappropriate to quantitatively describe the bioconcentration of surfactants because the most frequently used analytical method, LSC without prior chromatographic separation of radiolabeled compounds, does not allow to distinguish between the parent compound and metabolites” . In a second review from 2007, 38 measured BCF values for anionic surfactants representing 10 C 10 –C 13 LASs and 7 perfluoroalkyl acids were judged to be quantitatively reliable . There have since been several other BCF values published for LASs. Furthermore, BCF values from several unpublished industry studies have been reported, whereby few details are available on the methodology employed .…”
Section: Introductionmentioning
confidence: 99%